1999
DOI: 10.1093/emboj/18.10.2897
|View full text |Cite
|
Sign up to set email alerts
|

A developmental switch in H4 acetylation upstream of Xist plays a role in X chromosome inactivation

Abstract: L.P.O'Neill and A.M.Keohane contributed equally to this workWe have investigated the role of histone acetylation in X chromosome inactivation, focusing on its possible involvement in the regulation of Xist, an essential gene expressed only from the inactive X (Xi). We have identified a region of H4 hyperacetylation extending up to 120 kb upstream from the Xist somatic promoter P 1 . This domain includes the promoter P 0 , which gives rise to the unstable Xist transcript in undifferentiated cells. The hyperacet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
42
1
3

Year Published

2000
2000
2013
2013

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(49 citation statements)
references
References 78 publications
(113 reference statements)
3
42
1
3
Order By: Relevance
“…Here, we described that XIST expression was downregulated eightfold in TSA-treated embryos. This result agrees with the fact that deacetylation of coding regions of X-related genes and of the upstream promoter of XIST is essential for XCI, and HDAC inhibition prevents this and other XCI-related events, including XIST upregulation (O'Neill et al 1999). In this case, TSA might have prevented deacetylation of XIST promoter and also its upregulation, which in control group was already occurring.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Here, we described that XIST expression was downregulated eightfold in TSA-treated embryos. This result agrees with the fact that deacetylation of coding regions of X-related genes and of the upstream promoter of XIST is essential for XCI, and HDAC inhibition prevents this and other XCI-related events, including XIST upregulation (O'Neill et al 1999). In this case, TSA might have prevented deacetylation of XIST promoter and also its upregulation, which in control group was already occurring.…”
Section: Discussionsupporting
confidence: 87%
“…Therefore, in TSA-treated TSA affects XCI on IVF bovine blastocysts embryos, levels of H3k9ac were equalized, and average levels increased 2.2-fold. As deacetylation of X genes occurs at the onset of XCI process (O'Neill et al 1999), those low acetylated blastomeres found in control group might be more susceptible to XCI and XIST upregulation. Studies have revealed that TSA induces cell cycle arrest and apoptosis, by activating the expression of proapoptotic genes (Yakovlev et al 2010) and by opening chromatin structure, which becomes more susceptible to endonucleases (Koyama et al 2000).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…15,16 Collectively, these data indicate that histone acetylation/deacetylation is critical in the regulation of gene expression by transcription factors, as well as providing a powerful mechanism for epigenetic silencing of gene expression. Indeed, recent studies indicating that histone deacetylation plays an important role in X-chromosome inactivation support this contention, 17 while a link with DNA methylation has been demonstrated by the finding that some HDAC complexes contain DNA methyltransferases. [18][19][20][21] One important role for chromatin remodeling proteins in human disease has been highlighted by certain chromosomal translocations that feature in acute myeloid leukemias.…”
Section: Introductionmentioning
confidence: 98%
“…On Xi, Xist RNA coats the chromosome to repress Tsix expression; on Xa, Tsix RNA blocks Xist transcription and the Xist-mediated Xinactivation is therefore inhibited. Multiple studies have established that differential DNA methylation and histone modification states exist between Xi and Xa (Goto et al, 2002;Hansen, 2003;Heard et al, 2001;O'Neill et al, 1999). Xi is hypermethylated in CpG islands and in gene promoter regions, and displays histone H4 hypoacetylation (Allaman-Pillet et al, 1998;Jeppesen and Turner, 1993;Keohane et al, 1998).…”
Section: Epigenetic Developmental Phenomenamentioning
confidence: 99%